Pengaruh Kurikulum Outcome-Based Education (OBE) terhadap Kemampuan Literasi Sastra Mahasiswa PGSD di Universitas Muhammadiyah Jakarta - Mas Roro Diah Wahyu Lestari; Fitria Rosmi (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2026)
This study aims to determine the effect of implementing an Outcome-Based Education (OBE) curriculum on the literary literacy skills of students in the Elementary School Teacher Education (PGSD) program at Muhammadiyah University of Jakarta in the Literary Appreciation course. The low literary literacy skills of prospective elementary school teachers have become a major issue, highlighting the need for an outcome-based curriculum approach. This study employed a quantitative method with a quasi-experimental design (one-group pretest-posttest). The sample consisted of 44 second-semester students enrolled in the Literary Appreciation course. The instruments used included a short-answer test and an analysis assignment for poetry/short stories, both of which had been validated for validity and reliability. The results of the paired-sample t-test showed that the calculated t-value (3.601) was greater than the critical t-value (1.987), with a significance level of 0.01 < 0.05, thus rejecting the null hypothesis (H₀). The average increase in literary literacy scores between the pretest and posttest was 29.44 points, with a Cohen’s d value of 1.53, indicating a very strong effect. This study demonstrates that the application of OBE principles—such as clarity of focus, design down, high expectations, and expanded opportunities—through a CPL-based curriculum, authentic assessment, continuous feedback, and student portfolios significantly enhances literary literacy skills. These findings fill a gap in OBE research, which has long been dominated by the fields of engineering and English, and serve as a reference for PGSD study programs in designing outcome-based literature learning to support the BAPENAS 2035 target toward Quality Education.